Development of new stevia variety with high particular types of steviol glycosides for growing in Malaysia - Chiew, Miao Si (2018)
Stevia rebaudiana Bertoni from Asteraceae family is commercially valuable for its steviol glycosides(SGs) contents, which is 300 times sweeter than commercial sugar. However, the bottleneck in Malaysia is the lack of suitable stevia varieties that are able to thrive well under her climatic conditions and still produce high SGs. Mutation induction including gamma irradiation is effective in generating genetic variation and developing new plant varieties with desired traits. Hence, this study was aimed to determine the effects of acute and chronic gamma irradiation on phenotypic changes and enhancement of SGs contents of two selected stevia varieties, AKH L1 and UKMB40408. For acute gamma irradiation, in vitro shoot tip explants of stevia AKH L1 variety were subjected to a gamma doses regime of 10Gy to 50Gy, following which phenotypic changes of the irradiated explants and subsequent regenerated plantlets were observed. All irradiated explants exhibited different survival rates, with the lowest at 9.33±8.33% when subjected to 50Gy, while all the control (non-irradiated explants) survived. Acute irradiation at 50Gy was shown to result in poor plants growth and development with necrotic leaf morphology. The LD50 (dose resulting in 50% dead) was found to be at 23Gy. Subsequent irradiation of 900 shoot tip explants at 23Gy, and all surviving produced 468 surviving shoot tipswhich were all capable to develop and successfully subculture until the fourth generation, M4. TheseM4 in vitro mutant plantlets exhibited significant increased in the numbers of leaf (16.07±5.19) and average leaf size (1.12cm±0.26x0.54cm±0.15).High Performance Liquid Chromatography (HPLC) analysis performed in parallel further revealed the mutant plants contained higher concentrations of stevioside (387.04ppm), rebaudioside A (670.18ppm) and rebaudioside D (106.26ppm) compared to the non-irradiated plantlets which exhibited 96.87, 194.42 and 28.25ppm, respectively. Unfortunately, all the mutated in vitro stevia variety AKH L1 plantlets exhibited stunted growth after 12 sub-culturing cycles. In another parallel set of experiment with similar irradiation dose performed on 300 plantlets revealed that all samples failed to survive when acclimatized to glasshouse condition. All the roots exhibited poor histomorphological appearances such as loose cortex, loose vascular bundles and broken epidermal cells. Meanwhile, for the chronic irradiation, potted plants of stevia variety AKH L1subjected to a 10Gy to 50Gy doses regime showed that the suitable dose rate (Gy/hour) was 0.17Gy/h with LD50 of 35.5Gy. The irradiated potted plants exhibited increased plant height of 75.62±15.06cm and numbers of leaf of 43.5±3.54. Unfortunately, all 54 irradiated potted stevia AKH L1failed to survive one month after the irradiation event. Thus, the chronic experiment was repeated again with another steviavariety UKMB40408, which thrive well in Malaysia but possesses lower SGs contents. This stevia variety, when subjected to 30Gy to 50Gy, showed increased stevioside (149.92ppm, 150.13ppm, and 151.31ppm, respectively) and rebaudioside A (275.60ppm, 271.65ppm, and 272.17ppm, respectively) contents compared to stevioside (112.30ppm) and rebaudioside A (209.73ppm) of the control (non-irradiated). In conclusion, application of gamma irradiation did enhance the plant height, number of leaves, and SGs contents of stevia variety AKH L1, and also the SGs contents of stevia variety UKMB40408. This shows that gamma irradiation proved to be a useful, easy and rapid means of enhancing key traits in different stevia varieties.